Effect of noise during refurbishment work to surrounding / Mohd Yusri Ismail - Ismail, Mohd Yusri (Faculty of Architecture, Planning and Surveying, 2013)
This research has been made of study on the effect of noise during refurbishment work to the surrounding. The research also has a three objective to complete it. The purpose and objectives of the study are to identify, whether the use of equipment during refurbishment works cause noise pollution. To identify the equipment that produces noise and give recommendation of how to minimize the effect of noise during refurbishment works. This research, data collection will be collect based on the qualitative and quantitative data. Qualitative data have two category are primary data and secondary data. The primary data have include the interview and observation. Thus, secondary data have books, journal, articles and internet. Then, quantitative data have questionnaire, pilot study, sample population and survey instrument. This research also use pilot study to gather of data collection. Pilot study is questionnaire will be pre-test on a small population in each case studies before they reach the full sample. A pilot study can be helps the researcher to identify the questions derives the right information, phrases that confuse or test whether there are any words or determine if the instruction are clear for the participants and offend the respondent. Amount of 30 questionnaire was be use for pilot study before distribution actually it.